Coenzyme Q10 deficiency in elderly: Can nutritional supplementation play a role? Mini review - Carella, Angelo Michele; Marinelli, Teresa; Di Pumpo, Michele; Modola, Giovanni; Benvenuto, Angelo (The European Research Journal, 2019)
Coenzyme Q10 (CoQ10), an important mitochondrial redox component, plays a pivotal role in cellular energy production; moreover, it is the only lipid-soluble antioxidant endogenously synthesized in humans. Given its function and physiological importance, it is not surprising that CoQ10 deficiency may result in several diseases. With aging, humans begin to lose the ability to synthesize CoQ10 from food, resulting in reduced serum levels of CoQ10 and contributing to aging-associated symptoms. Poor eating habits, infections, stress and also some drugs, as beta blockers, antihypertensive agents and statns, may reduce serum levels of CoQ10. Dietary supplementation has been proposed as key strategy to increase CoQ10 availability, improving health status in elderly; however CoQ10 is not approved by U.S. Food and Drug Administration for the treatment of any medical condition and it is sold only as a dietary supplement. Aim of the study was to examine the latest relevant evidences on potential benefits of CoQ10 nutritional supplement and its implication in improving health status in elderly. There is evidence that, in elderly, oral administration of CoQ10 reduces oxidative stress and inflammatory markers and reduces cardiovascular mortality; in diabetics CoQ10 treatment improves insulin sensitivity and decreases glycated hemoglobin. Therapeutic benefit from CoQ10 supplementation has also been obtained in neurodegenerative diseases as Parkinson’s, Alzheimer’s and Huntington's diseases. CoQ10 supplements could be useful in several aging- related clinical conditions; however, well standardized long-term and larger further studies are needed.